Rediseño y construcción del simulador de accidentes eléctricos - Romero, O. (2010)
This article shows simulations of electrical accidents in hospitals, which arises from the need to teach how an electric shock produced by a ground fault current affects and causes different type of consequences for patients. In this way we prove that these dangers are latent and can be avoided by creating and implementing security processes in order to prevent these kinds of events. The project is to redesign the electrical accident simulator that currently exists, which is obsolete because it finds that the electrical devices and electronic components used in the simulator are actually in poor condition.